2014
DOI: 10.4238/2014.august.26.6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic distances and phylogenetic trees of different Awassi sheep populations based on DNA sequencing

Abstract: ABSTRACT. This study aimed to estimate evolutionary distances and to reconstruct phylogeny trees between different Awassi sheep populations. Thirty-two sheep individuals from three different geographical areas of Jordan and the Kingdom of Saudi Arabia (KSA) were randomly sampled. DNA was extracted from the tissue samples and sequenced using the T7 promoter universal primer. Different phylogenetic trees were reconstructed from 0.64-kb DNA sequences using the MEGA software with the best general time reverse dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Additionally, the admixture could be result of the high flow of genes between farms due to the practice to borrow or lease rams and lack of effective control in breeding programs [25] in Bulgaria. Similar results have been reported by Stahlberger-Saibetkova et al [7] and Al-Atiyat et al [32]. However, lower estimates of genetic differentiation between sheep breeds were found by Ocampo et al [25], Bozzi et al [5], Zhong et al [30], Álvarez et al [33], Ben Sassi et al [34], Hoda et al [14] and Abdelkader et al [35], who reported Fst ranging between 0.05 and 0.3.…”
Section: Population Genetic Diversitysupporting
confidence: 79%
“…Additionally, the admixture could be result of the high flow of genes between farms due to the practice to borrow or lease rams and lack of effective control in breeding programs [25] in Bulgaria. Similar results have been reported by Stahlberger-Saibetkova et al [7] and Al-Atiyat et al [32]. However, lower estimates of genetic differentiation between sheep breeds were found by Ocampo et al [25], Bozzi et al [5], Zhong et al [30], Álvarez et al [33], Ben Sassi et al [34], Hoda et al [14] and Abdelkader et al [35], who reported Fst ranging between 0.05 and 0.3.…”
Section: Population Genetic Diversitysupporting
confidence: 79%
“…Some recent studies have highlighted the genetic diversity of KSA sheep (Aljumaah et al, 2014 ; Adam et al, 2015 ). In addition, some studies have showed their differentiation from Jordan Awassi (Al-Atiyat and Aljumaah, 2014 ) and from Egypt and worldwide sheep (Peter et al, 2007 ). However, none of these studies provided information on the genetic structure of the local KSA sheep populations.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of its available sequences were too short to be included in this study, resulting in its low number of samples inside our dataset, the majority of which come from Pakistan. We hypothesize that this breed, which is largely spread in the Near East, could have some ecotypes [ 47 ] connected to Egyptian breeds, as found by Ahbara et al [ 11 ] through their 50K SNP BeadChip analyses, and more specifically to Rahmani and Barki [ 48 ].…”
Section: Discussionmentioning
confidence: 99%